Skin and Wound Care in Lymphedema Patients: A Taxonomy, Primer, and Literature Review. (July 2017) - Fife, Caroline E.; Farrow, Wade; Hebert, Adelaide A.; Armer, Nathan C.; Stewart, Bob R.; Cormier, Janice N.; Armer, Jane M.
ABSTRACT: BACKGROUND: Lymphedema is a condition of localized protein-rich swelling from damaged or malfunctioning lymphatics. Because the immune system is compromised, there is a high risk of infection. Infection in patients with lymphedema may present in a variety of ways. OBJECTIVE: The goals of this review were to standardize the terminology of skin breakdown in the context of lymphedema, synthesize the available information to create best practice recommendations in support of the American Lymphedema Framework Project update to its Best Practices document, and create recommendations for further research. DATA SOURCES: Publications on skin care and wounds were retrieved, summarized, and evaluated by a team of investigators and clinical experts. STUDY SELECTION AND DATA EXTRACTION: Terms for lymphedema-associated skin breakdown were compiled and paired with photographs of commonly noted skin changes among patients with lymphedema. A list of standard dermatological terms was created. A more extensive literature search was then conducted by all authors. DATA SYNTHESIS: Skin disorders associated with lymphedema have been classified into 5 categories. Descriptions, photographs, and recommendations for treatment are presented. CONCLUSIONS: Skin care is an important defense against infection. Because of the lack of research, a consensus of thought and content leaders' opinion should guide the best practices for wound care in lymphedema.